Operative treatment of III grade open fractures of the tibial diaphysis - Kaftandjiev I; Pejkova S; Saveski J (Macedonian Academy of Sciences and Arts, 2006)
Open fractures, especially III grade open fractures of the tibial diaphysis, according to the Gustilo classification still remains a serious therapeutic problem. The aim of the study was to evaluate the clinical results after operative treatment of III grade open fractures of diaphysis of the tibia and to promote a new method of fracture fixation.